A new educational paradigm for the 21st century. Issue 2 (20th December 2019) - Cunningham, Ian
Abstract : Purpose: This paper calls for a New Educational Paradigm in which young people are supported through an educational process that assists them to take charge of their own learning. A process in which they choose what they want to learn and how rather than the current system that requires them to regurgitate facts in order to pass tests/exams. Design/methodology/approach: A viewpoint based on the author's experience of running the Self Managed Learning College in the UK for the past 20 years and his forthcoming book detailing the research evidence that highlights the need for change. Findings: Businesses complain that the education system does not currently equip young people with the skills they need to thrive in the ever-changing world of work. The system needs to change and business leaders need to get involved. The College is one example of many around the world where people are deciding to get away from the rigidities, inappropriateness and waste of the current system. Originality/value: The College is a unique environment which has been successfully operating for 20 years. The operating processes of the College match the outcomes needed in the working world and wider society. It provides an exemplar of how to help young people take responsibility for their own learning in order for them to lead a good life in the future.